The environmental cofactors in carcinogenesis in high risk HPV/HIV-positive women - Paulo,Michele (2007)
The objective of the present study was to assess the presence of human papilloma virus (HPV) in HIV-infected women, with comparison between the Papanicolaou cytologic technique and the molecular PCR technique, as well as to determine the type of HPV, to measure cellular immunocompetence and to identify the presence of risk factors for the acquisition of HPV infection. Thirty HIV-infected women were selected. Vaginal and endocervical samples were collected from 27 of them. The smears were examined by 3 experienced cytologists to diagnose the presence of HPV by the Papanicolaou technique and the results were compared to HPV detection and typing by PCR. HPV-infected patients were interviewed in order to identify the presence of risk factors for the acquisition of the virus. Eight of the 27 patients analyzed (29%) presented HPV in endocervical samples submitted to PCR, 6 of them (75%) presented HPV involving a high risk of development of cervical cancer. For 5 of these patients, the cytologic diagnosis was not confirmed by PCR. When cellular immunocompetence was related to HPV infection, PCR revealed a diagnosis of HPV in 37.50% of the patients at intermediate risk for HPV infection and in 83.33% of the patients at high risk for HPV infection. These immunologically compromised HPV-infected patients are at higher risk of developing cervical neoplasia. We showed here that PCR is adequate for HPV detection and that, if only the Papanicolaou method is used for the follow-up of these patients, we will not provide good prevention of cervical cancer.